Autobiographical Accounts of Students' Experiences Learning Mathematics: A Review. Issue 3 (3rd July 2017) - Towers, Jo; Hall, Jennifer; Rapke, Tina; Martin, Lyndon C.; Andrews, Heather
ABSTRACT: In this article, we review published literature that draws on autobiographical accounts of students' experiences learning mathematics. We summarize the main findings of the target literature and present recommendations for further research that will extend this field. Our review indicates that autobiographical and narrative methodological approaches have the potential to occasion important advances in our knowledge of students' experiences learning mathematics. However, relative to accounts of preservice teacher learning, there is a paucity of published research that documents the mathematics learning experiences of kindergarten to Grade 12 students.